First record of myrcia magna D.Legrand (Myrtaceae) as a myrmecophyte host for myrcidris epicharis ward, 1990 (Formicidae: Pseudomyrmecinae) - Gaem, Paulo Henrique (2019)
The association of the ant Myrcidris epicharis with the plant Myrcia magna is reported for the first time. This association was registered in two localities along the Negro river basin, in the region of Manaus, Amazonas state, Brazil. The ants inhabit swollen shoots in apical and subjacent nodes of the branches. This record represents the second plant species of Myrtaceae to be associated with Myrcidris epicharis. © 2019 Universidade Estadual de Feira de Santana. All rights reserved.